1993
DOI: 10.1016/0304-3959(93)90104-w
|View full text |Cite
|
Sign up to set email alerts
|

Is TENS purely a placebo effect? A controlled study on chronic low back pain

Abstract: Although high-frequency low-intensity transcutaneous electric nerve stimulation (TENS) has been extensively used to relieve low back pain, experimental studies of its effectiveness have yielded contradictory findings mainly due to methodological problems in pain evaluation and placebo control. In the present study, separate visual analog scales (VAS) were used to measure the sensory-discriminative and motivational-affective components of low back pain. Forty-two subjects were randomly assigned to 1 of 3 groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
113
1
4

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(123 citation statements)
references
References 44 publications
4
113
1
4
Order By: Relevance
“…Perhaps more important is the fact that our findings clearly show that TENS significantly decreased pain intensity ratings in a cumulative manner over repeated treatment sessions, in contrast to animal research, where repeated TENS administration results in gradual diminution of analgesic effect via opioid tolerance [19], but (except for the sham TENS) in line with the results of Marchand et al [10]. However, how much the pain results will improve when extending the treatment period needs to be investigated.…”
Section: Comparison Of Our Results With Those Of Other Tens Studies Isupporting
confidence: 64%
See 1 more Smart Citation
“…Perhaps more important is the fact that our findings clearly show that TENS significantly decreased pain intensity ratings in a cumulative manner over repeated treatment sessions, in contrast to animal research, where repeated TENS administration results in gradual diminution of analgesic effect via opioid tolerance [19], but (except for the sham TENS) in line with the results of Marchand et al [10]. However, how much the pain results will improve when extending the treatment period needs to be investigated.…”
Section: Comparison Of Our Results With Those Of Other Tens Studies Isupporting
confidence: 64%
“…A 50% change in pain intensity has been used to evaluate TENS treatment effect in patients with osteoarthritis; Smith et al [9] found 50% or more relief in pain intensity in 67% and 27% of the patients treated with TENS and sham TENS respectively; treatment was applied 8 times for 20 min over a period of 4 weeks. However, Marchand et al [10] found in patients with low back pain that TENS significantly decreased intensity ratings in a cumulative manner over repeated treatment sessions. So for shorter periods of TENS treatment, less pain reduction may be expected than for longer treatment periods.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,9,11 ± 13 Management of associated complaints such as sleep disturbance, 13 speci®c type of pain 2 ± 5 or depression 6,7 increases the reliance on medication, 8 some of which is contentious for long term use. 14 The most familiar non-pharmaceutical alternative for pain management, transcutaneous electrical nerve stimulation (TENS), is of limited use in chronic pain 15 such as that associated with SCI. A variant, spinal cord stimulation, has been used for 30 years, 16 but there remains a lack of consistent proof of e cacy and cost e ectiveness, and some studies 17,18 report the development of tolerance with resultant loss of analgesic e cacy.…”
Section: Introductionmentioning
confidence: 99%
“…It was conc lu ded that the ef fect of TENS las ted short and TENS sho uld be app li ed in a mul ti dis cip li nary ap pro ach com bi ned with ot her phar ma co lo gic agents. 13 TENS is a fre qu ently app li ed the rapy in chronic pa in alt ho ugh evi den ce for ef fec ti ve ness is inconc lu si ve. Se ve ral types of TENS exist, ba sed on dif fe rent com bi na ti ons of fre qu ency, pul se du ra tion and in ten sity.…”
Section: Discussionmentioning
confidence: 99%